Trends in Severe Pediatric Emergency Conditions in a National Cohort, 2008 to 2014. Issue 11 (November 2020) - Michelson, Kenneth A.; Hudgins, Joel D.; Burke, Laura G.; Lyons, Todd W.; Monuteaux, Michael C.; Bachur, Richard G.; Finkelstein, Jonathan A.
Abstract : Objective: The objective of this study was to determine the incidence and recent trends in serious pediatric emergency conditions. Methods: We conducted a cross-sectional study of the Nationwide Emergency Department Sample from 2008 through 2014, and included patients with age below 18 years with a serious condition, defined as each diagnosis group in the diagnosis grouping system with a severity classification system score of 5. We calculated national incidences for each serious condition using annualized weighted condition counts divided by annual United States census child population counts. We determined the highest-incidence serious conditions over the study period and calculated percentage changes between 2008 and 2014 for each serious condition using a Poisson model. Results: The 2008 incidence of serious conditions across the national child population was 1721 visits per million person-years (95% confidence interval, 1485–1957). This incidence increased to 2020 visits per million person-years (95% confidence interval, 1661–2379) in 2014. The most common serious conditions were serious respiratory diseases, septicemia, and serious neurologic diseases. Anaphylaxis was the condition with the largest change, increasing by 147%, from 101 to 249 visits per million person-years. Conclusions: The most common serious condition in children presenting to United States emergency departments is serious respiratory disease. Anaphylaxis is the fastest increasing serious condition. Additional research attention to these diagnoses is warranted.